Study of Pyrotechnic Disc Materials in Thermal Batteriesby X-Ray Technique - H. HUSSEIN, FALAH; N. ALKHATEEB, AHMED; M. SARHAN, WALEED; D. OMRAN, KAREEM (Asian Journal of Chemistry, 2010)
In this investigation, a comparative X-ray study for the pyrotechnic disc of the assembled cell has been carried out. The results were compared with those issued by the American Society for Testing Materials (ASTM). For this, the X-ray diffraction and the linear Spectrum for this diffraction, belonging to the mixture used in industrialization of pyrotechnic disc of the thermal cell before ignition, has been accomplished. Peaks belonging to the fuel, Fe and the oxidizer, KCIO4, components were developed, indicating that the two components were incorporating in the composition of the pyrotechnic disc. Furthermore, another comparison for the X-ray diffraction values and the linear spectrum of this diffraction, for the thermal mixture after ignition, was brought about. Peaks pertaining to Fe2O3, KCl and ZrO have emerged, demonstrating that oxidation and reduction processes have taken place, where the mentioned products were formed by the reaction among Fe, Zr and KCIO4. The formation of ZrO revealed that Zr induded in the composition of the active disc could be detected before ignition due to its low concentration.